General stratigraphic framework of the Quaternary in Eastern Canada - Prest, V. (Géographie physique et Quaternaire, 1977)
In eastern Canada, inter-glacial and interstadial deposits have been reported from Nova Scotia and Québec, but in the other provinces only Wisconsinan deposits. In Nova Scotia, pollen from some organic deposits buried beneath one or more tills, indicates a warm, interglacial climate — presumably the Sangamon Interglacial Interval. Other buried organic deposits, in contrast, indicate a cool, boreal forest environment. As radiocarbon analyses have given 'greater than' dates the deposits are considered to be early Wisconsinan. The interval is tentatively correlated with the St. Pierre Interstadial of Québec. The only known mid-Wisconsinan deposit is at Salmon River on St. Mary's Bay, in southwestern Nova Scotia, where the marine shells have been dated at 38,600,4C years. Elsewhere in both coastal and interior Nova Scotia multiple till sections suggest a more or less continuous ice cover through-out the Wisconsinan. In central Nova Scotia, however, red tills have been considered late-Wisconsinan. In Québec, there is a very limited, but nevertheless important, record of the Sangamon Interglacial Interval. Compact clayey rhythmites in the Harricana River Basin, close to James Bay, appear to correlate with the lacustrine member of the Missinaibi Formation farther west in Ontario. In southern Québec, there is another indication of interglacial deposits for the oldest sediments exposed in the Sherbrooke region and in the Upper Chaudière River Valley beneath the lowest of three Wisconsinan tills. These deposits were weathered and cemented prior to deposition of the oldest till. As the gravels contain pebbles of Laurentian Shield gneiss there obviously was a pre-Sangamon glaciation. These two areas contain the most complete stratigraphie record of the Wisconsinan yet established in Québec.